Răspuns :
Se ia fiecare dintre termeni si se egaleaza pe rand cu 0.
x^2-4= 0
x^2 = 4, deci x = +2 si -2
8-x^2 = 0
x^2 = 8, deci x = + 2√2 si - 2√2
x^2-4= 0
x^2 = 4, deci x = +2 si -2
8-x^2 = 0
x^2 = 8, deci x = + 2√2 si - 2√2
[tex](x^{2}-4)(8-x^{2})=0[/tex]
[tex]~ \ ~[/tex]
[tex]x^{2}-4=0[/tex]
[tex]8-x^{2}=0[/tex]
[tex]~ \\ ~[/tex]
[tex]x=2[/tex]
[tex]x=-2[/tex]
[tex]x=2\sqrt{2}[/tex]
[tex]x=-2\sqrt{2}[/tex]
[tex]~ \\ ~[/tex]
[tex]x_{1}=-2\sqrt{2}[/tex]
[tex]x_{2}=-2[/tex]
[tex]x_{3}=2[/tex]
[tex]x_{4}=2\sqrt{2}[/tex]
[tex]~ \ ~[/tex]
[tex]x^{2}-4=0[/tex]
[tex]8-x^{2}=0[/tex]
[tex]~ \\ ~[/tex]
[tex]x=2[/tex]
[tex]x=-2[/tex]
[tex]x=2\sqrt{2}[/tex]
[tex]x=-2\sqrt{2}[/tex]
[tex]~ \\ ~[/tex]
[tex]x_{1}=-2\sqrt{2}[/tex]
[tex]x_{2}=-2[/tex]
[tex]x_{3}=2[/tex]
[tex]x_{4}=2\sqrt{2}[/tex]